Modificación del proceso de reducción expansiva para la síntesis de nanopartículas de hierro - Rodríguez, Adriana L.; Departamento de Ingeniería Química y Ambiental, Facultad de Ingeniería, Universidad Nacional de Colombia, Bogotá, Colombia. (2014)
The reductive expansion method has been used successfully in the synthesis of metal nanoparticles. However, there are no reports regarding the use of expansion methods to produce oxidized nanoparticles. Here, we propose an adjustment to the current oxidizing atmosphere application during reductive expansion. Mixtures of different weight ratios of iron nitrogen salts and urea (blowing agent) were subjected to thermal shock in an oven; the sudden sublimation of the urea and nitrogen salts originated a fine dispersion of material that came into contact with reducing gases. During this sublimation, metallic iron nanoparticles were produced and subsequently oxidized by the prevailing oxidizing atmosphere. Through characterization using X-ray diffraction, we determined that the crystalline phase of the formed nanoparticles depends on the composition of the reactants. In contrast, particle size distribution, surface area and oil absorption are not strongly influenced by this composition.